The first human fossil from the Ruidera site (Castilla-La Mancha, Spain): A partial parietal and its implications for Middle Pleistocene hominin variability in Southern Europe - D. García-Martínez; C. Buenestado Ruíz; S. Díaz Pérez; M. Bastir; L. Bermejo Albarrán; I. Campaña; O. Cambra-Moo; G. Cifuentes-Alcobendas; M. del Val; M. Duval; M.D. D'Angelo del Campo; B. Fernández Cascón; et al. (Journal of Human Evolution, 2026)

Hunting Iberian ibex: from a threat factor to a conservation tool - Jesús M. Pérez; Fabiola Mesa-Pérez; María J. Fernández-Muñoz; José E. Granados; Paulino Fandos; Ramón C. Soriguer; Pelayo Acevedo; Pablo Refoyo; Enrique Barreñada; Juan Carlos Peral; Alberto Fernández-Arias; José A. Martínez; et al. (European Journal of Wildlife Research, 2025)
In this study we have compiled the information from official databases about Iberian ibex, Capra pyrenaica , hunting yields, hunting trophies and hunting licenses in the Spanish regions where the species is present and hunted. Such quotas showed an increasing trend between 2005–2021 and, on average, during this period, ≈ 6400 animals were yearly harvested. Despite this number decreased in 2019 and 2020 (in this last year, mainly due to the lock down caused by the COVID pandemia), the annual quota raised, reaching over 12,000 ibexes in 2021. The number of trophies increased since the 1970s and peaked in the period 2001–2005, and then declined during the period 2006–2020. At national level, the number of hunting licenses decreased from 2006 to 2021 by a 36.5%. The regional average hunting yield was significantly correlated with a regional-based ibex abundance estimation. The current situation of continued population increase together with the trophy reduction might suggest that the overall population is exceeding the carrying capacity. In this context, if hunting activity was one of the main factors involved in local extinction of the species, currently it should be considered a tool for sustainable managing of ibex populations in an scenario of increasing demographic trends and generalized absence of predators.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)